Personnel policy: issues and practices : issues and practices - Odiorne, George S. (Columbus, Ohio : C. E. Merrill Books, 1963)
This book is written for the wide variety of persons concerned with personnel policy. Such persons may be academic students of business administration, labor economics, personnel management, or industrial engineering. They may also be general business students who have objectives other than professional training in personnel who want to know about the broad policy matters concerning personnel and manpower management.
Includes index.
Includes bibliographical references p.498-512
hza 19/07/2018
Loan
Keywords: Personnel management